Voices from the Warsaw Ghetto : writing our history - Roskies, David G. 1948- HerausgeberIn VerfasserIn einer Einleitung; Kassow, Samuel D. 1946- VerfasserIn eines Vorworts (Yale University Press, 2019)
Oyneg Shabes / Emanuel Ringelblum -- Telephone / Władysław Szlengel -- I speak to your openly, child / Josef Kirman -- Ghetto folklore / Shimon Huberband -- House no. 21 / Peretz Opoczynski -- Chronicle of a single day / Leyb Goldin -- From scroll of agony / Chaim A. Kaplan -- Charcoal and watercolor sketches (1939-42) / Gela Seksztajn -- The little smuggler / Henryka Łazowert -- Hershek / Stepania Gradzińska -- Song of hunger and songs of the cold / Yitzhak Katzenelson -- From holy fire / Rabbi Kalonymus Shapira -- From the Notebooks and diary of the great deportation / Abraham Lewin -- Last testament / Israel Lichtenstein -- What can I possibly say and ask for at this moment? / Gela Seksztajn -- 4580 / Yehoshue Perle -- Things and counterattack / Władysław Szlengle -- The ghetto in flames / "Maor" -- Yizkor, 1943 / Rachel Auerbach.